Kingship Christology: A reflection on Midnight Crew’s “Igwe” within the Igbo Socio-Cultural Context - Boaheng, Isaac (Indonesian Academy of Social and Religious Research (IASRR), 2024)
This literature-based research explored the subject of Kingship Christology as portrayed in Midnight Crew’s song “Igwe.” Through an interdisciplinary approach, the paper delved into how the song articulates the Kingship of Christ from an Igbo Christian perspective. The paper critically examined the lyrics of the song, linking it with the Christian and Igbo socio-cultural worldviews. The research established that Jesus surpasses every human king (past, present and future) in every human society and serves as a perfect King whose leadership style provides a perfect model of what human leadership ought to be. This finding formed the basis for exploring key implications of Jesus’ kingship for the Igbo/African sociopolitical setting. The paper charged African leaders to adopt a Christological model of leadership characterized by humility, servanthood, transparency, accountability, inclusivity, and a deep commitment to the welfare of their communities. In addition to demonstrating the nexus between music, theology and culture, the paper contributes to African Christian scholarship on Christology, musical theology and leadership.